Childcare Assistance: Are Subsidies or Tax Credits Better?1. (23rd February 2017) - Gong, Xiaodong; Breunig, Robert
Abstract: We evaluate price subsidies and tax credits for childcare. We focus on partnered women's labour supply, household income and welfare, demand for childcare and government expenditure. Using Australian data, we estimate a joint, discrete structural model of labour supply and childcare demand. We introduce two methodological innovations – a more flexible quantity constraint that total formal and informal childcare hours are at least as large as the mother's labour supply and the explicit inclusion of maternal childcare in the utility function as a proxy for child development. We find that tax credits are more effective than subsidies in terms of increasing average hours worked and household income. However, tax credits disproportionately benefit wealthier and more educated women. Price subsidies, while less efficient, have positive redistributional effects.